2018
DOI: 10.1039/c7cp06546a
|View full text |Cite
|
Sign up to set email alerts
|

The anharmonic quartic force field infrared spectra of hydrogenated and methylated PAHs

Abstract: Polycyclic aromatic hydrocarbons (PAHs) have been shown to be ubiquitous in a large variety of distinct astrophysical environments and are therefore of great interest to astronomers. The majority of these findings are based on theoretically predicted spectra, which make use of scaled DFT harmonic frequencies for band positions and the double harmonic approximation for intensities. However, these approximations have been shown to fail at predicting high-resolution gas-phase infrared spectra accurately, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 37 publications
(48 reference statements)
3
63
0
Order By: Relevance
“…We believe that this transition is a combination mode similar to the transitions in PAHs above 1700 cm -1 as calculated in Ref. 63.…”
Section: Infrared Spectra Of Pure Ace Complexessupporting
confidence: 80%
“…We believe that this transition is a combination mode similar to the transitions in PAHs above 1700 cm -1 as calculated in Ref. 63.…”
Section: Infrared Spectra Of Pure Ace Complexessupporting
confidence: 80%
“…Once the QFF is known, the energy of the anharmonic vibrational states can be written as E(v)=kωktrue(vk+12true)+klχkltrue(vk+12true)true(vl+12true) where χ kl are the anharmonic constants (see Ref. for a detailed explanation). VPT2 is a powerful method but it is affected by resonances, that is, instances where the sum/difference/combination of some harmonic mode energies are nearly equal.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For each polyad a matrix is built, containing the relevant anharmonic constants, and is diagonalised. The resulting eigenvectors give the degree of mixing of the states, while the eigenvalues give the new energies of the states …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, the application of VPT2 to PAHs shows appreciable discrepancy in comparison to experimental spectra, which could be due to the improper choice of functionals and basis sets. It has been reported that for hydrogenated and methylated PAHs, changing from B971/TZ2P to B3LYP/N07D, the improvement in agreement between theory and experiment was found to be from an error of 1% down to 0.1% (30-3 cm −1 in the CH-stretching region; Mackie et al 2018).…”
Section: Introductionmentioning
confidence: 98%